ANALISIS HOTSPOT DI KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - Isna Abelia; Elvi Zuriyani; Rika Despica (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the spatial distribution of hotspots, identify the factors causing fires, assess mitigation efforts, and assess the impact of hotspot phenomena on the environment and society in Koto Baru District, Dharmasraya Regency in 2024. The method used is descriptive qualitative with field observation approaches, interviews, questionnaires, and spatial data analysis using satellite imagery and ArcGIS software. The results showed that the distribution of the most hotspots was in Nagari Koto Padang (52%), followed by Nagari Koto Baru (30%), Nagari Ampang Kuranji (17%), while Nagari Sialang Gaung had no hotspots (0%). The factors causing fires include physical factors, such as forest residues (twigs and dry leaves), and social factors, such as agricultural residues (straw and husks). Mitigation efforts were carried out through the use of firefighting equipment by the community (75%), technical training for volunteers, improvement of firefighting facilities, and education in vulnerable areas, although still hampered by difficult terrain, limited personnel, and low early reporting. The hotspot phenomenon has resulted in ecosystem damage, biodiversity loss, increased cases of acute respiratory infections (ARI), and disruption to socio-economic activities. These findings underscore the need for strengthened early warning systems, cross-sector coordination, and active community participation to mitigate forest and land fires sustainably.